2019
DOI: 10.1182/blood-2019-123560
|View full text |Cite
|
Sign up to set email alerts
|

Subcutaneous Daratumumab Plus Standard Treatment Regimens in Patients with Multiple Myeloma across Lines of Therapy: Pleiades Study Update

Abstract: Introduction : Daratumumab (DARA) 16 mg/kg intravenous (IV) is approved as monotherapy for relapsed or refractory multiple myeloma (RRMM) and in combination with standard-of-care regimens for transplant-ineligible newly diagnosed multiple myeloma (NDMM). A subcutaneous (SC) co-formulation of DARA (DARA SC; 1,800 mg) with recombinant human hyaluronidase PH20 (rHuPH20; ENHANZE® drug delivery technology, Halozyme, Inc.) is under investigation in a number of ongoing studies. In the phase 3 COLUMBA study, DARA SC w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…As in the COLUMBA study, the bodyweight subgroup analysis in the PLEAIDES study found the lowest bodyweight subgroups (⩽65 kg) had higher C trough , and the heaviest bodyweight subgroups had lower C trough , with Dara-SC across the D-VRd, D-VMP, and D-Rd cohorts. 16 However, the mean C trough at the end of weekly dosing was above the previously determined recommended target saturation for Dara-IV 19 across all cohorts, and as discussed previously, the ORRs of the Dara-SC combination therapies in the PLEAIDES study were comparable with those with Dara-IV reported previously. Based on the results of the bodyweight subgroup analyses in COLUMBA and PLEAIDES, bodyweight does not appear to have a clinically significant effect on the safety or efficacy of fixed-dose Dara-SC.…”
Section: Subcutaneous Daratumumab In Systemic Light-chain (Al) Amyloidosissupporting
confidence: 81%
See 2 more Smart Citations
“…As in the COLUMBA study, the bodyweight subgroup analysis in the PLEAIDES study found the lowest bodyweight subgroups (⩽65 kg) had higher C trough , and the heaviest bodyweight subgroups had lower C trough , with Dara-SC across the D-VRd, D-VMP, and D-Rd cohorts. 16 However, the mean C trough at the end of weekly dosing was above the previously determined recommended target saturation for Dara-IV 19 across all cohorts, and as discussed previously, the ORRs of the Dara-SC combination therapies in the PLEAIDES study were comparable with those with Dara-IV reported previously. Based on the results of the bodyweight subgroup analyses in COLUMBA and PLEAIDES, bodyweight does not appear to have a clinically significant effect on the safety or efficacy of fixed-dose Dara-SC.…”
Section: Subcutaneous Daratumumab In Systemic Light-chain (Al) Amyloidosissupporting
confidence: 81%
“…Moreover, Dara-SC in clinical trials has been shown to have comparable efficacy and a similar safety profile to the intravenous formulation, with significantly lower rates of IRRs, making Dara-SC a favorable treatment option. [14][15][16] Here, we review the first in-human study of Dara-SC (PAVO) that assessed the safety and pharmacokinetics (PK) of subcutaneous daratumumab, and the phase III COLUMBA and phase II PLEAIDES trials that led to the approval of Dara-SC. We also highlight important clinical considerations for the use of Dara-SC and provide practical guidelines for the administration of Dara-SC in the clinic.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides establishing the efficacy of monotherapy SC daratumumab monotherapy, there are other ongoing trials examining the efficacy of SC daratumumab in combination with other novel agents PLEIADES (NCT03412565) is a phase II trial that is currently adding SC daratumumab to various standard regimens (VRd, VMP, Rd, and Kd). 79 So far results reveal that SC daratumumab leads to similar efficacy as the IV formulation. Outcomes here will compare the treatment arms to phase III data on the established agents without daratumumab to again see how these novel regimens will help patients achieve a PR or better.…”
Section: Future Role and Applications Sc Daratumumabmentioning
confidence: 98%